Drone-assisted augmentation of the parasitoid Anagyrus lopezi for cassava mealybug control in Indonesia - MUHAMMAD ALIMUN WASIK; DEWI SARTIAMI; ALI NURMANSYAH (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Wasik MA, Sartiami D, Nurmansyah A. 2025. Drone-assisted augmentation of the parasitoid Anagyrus lopezi for cassava mealybug control in Indonesia. Biodiversitas 26: 6437-6446. The cassava mealybug, Phenacoccus manihoti, is an invasive pest that causes severe damage and economic loss in cassava production in Indonesia. Biological control using the parasitoid Anagyrus lopezi to manage P. manihoti has proven effective; however, its manual releases remain constrained by time, labor, and cost. This study evaluated the effectiveness and operational efficiency of A. lopezi augmentation using drone-assisted and manual release techniques in cassava fields. Effectiveness was measured by the parasitism rate of A. lopezi on P. manihoti, while efficiency was assessed through cost and time analyses. The augmentation treatment significantly increased the parasitism rate (F = 1955.78; df = 2,11; p<0.001). Parasitism rates under both release techniques were 47.18±0.92% for drones and 46.87±1.04% for manual release, compared with 16.11±0.59% in the control plots. The comparable parasitism rates achieved by drone-assisted and manual releases indicate that drone deployment maintains comparable biological effectiveness to manual augmentation. Moreover, drone application requires only 25 minutes per hectare, compared to 200 minutes per hectare manually. Although the initial cost of drone use was higher at small operational scales, economic analysis indicated a break-even point at approximately 25 ha. These findings demonstrate the feasibility of drone-assisted parasitoid deployment as an operationally efficient approach for large-scale biological control of P. manihoti. This contribution strengthens area-wide Integrated Pest Management (IPM) programs by enabling synchronized parasitoid augmentation while also supporting the broader development of smart-agriculture technologies for cassava-based farming systems.